Implementation of the District Integrated Administrative Services Policy - Afwa Magfhirah Saleh; Andi Cudai Nur; Herman Herman (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The new service paradigm emphasizes community satisfaction, especially in the millennial era who are critical of government administration. This research aims to evaluate the effectiveness of this thesis program entitled Implementation of the District Integrated Administrative Services Policy in Lilirilau District, Soppeng Regency, which is motivated by the government's desire to bring closer, simplify and speed up licensing/non-licensing administration services at the sub-district level. The data collection technique is to use observation, interview and documentation techniques. Meanwhile, data analysis techniques use data reduction, data presentation and drawing conclusions. Based on the results of the analysis, it can be concluded that there are three District Integrated Administrative Services policies in Lilirilau District that have been implemented well and there are three that have not been implemented well and provide benefits to the community, especially regarding administrative services. The implementation of PATEN in Lilirilau sub-district is also in accordance with applicable provisions as mandated by Minister of Home Affairs Regulation Number 04 of 2010 concerning Guidelines for District Integrated Administrative Services. Even though in its implementation there are several shortcomings that need attention, such as standards & policies, resources and disposition, basically these three indicators are important factors in the implementation of PATEN which cause obstacles to the service process at the Lilirilau sub-district office. This research will not only provide an academic contribution, but can also be a basis for local governments to formulate strategies for improving public services that are more effective and responsive to community needs.